Pemberdayaan Usaha Mikro Melalui Identitas Marek Dan Strategi Digital Marketing Pada UMKM Nasi Bakar Di Kelurahan Kepanjen Kidul Kota Blitar - Dewi Puspa Arum; Ananda Nabila Laraswari; Alifah Rizky Wiyanti; Cita Devi Ainaya; Devi Khoiriyah; Farras Dewi Yuanita; Junita Pramita Sari (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
MSMEs are one of the pillars of the national economy which must get the main opportunity, support, protection and development as wide as possible as a form of firm alignment with the people's economic business group without ignoring the role of big business. The purpose of this KKN activity is to provide assistance regarding digital marketing, especially through social media, for roasted rice micro businesses in Kepanjen Kidul Village, Blitar City to increase sales of these products.The method used is descriptive method with a qualitative approach. The descriptive method is used to describe the efforts of UMKM Nasi Bakar "Pak Githu" in developing its marketing with digital marketing. While a qualitative approach is used to explain the process of implementing digital marketing in line with the development of its business.The mentoring work program carried out for Nasi Bakar SMEs is to rebrand products, make labels and business cards, utilize digital marketing, carry out digital content creation. Through a strong brand identity and an effective digital marketing strategy, Nasi Bakar MSMEs in the Kepanjen Kidul Village can experience significant empowerment.